From Stress to Screens: How Internet Use, Loneliness, and Social Media Habits Relate to Cyberbullying Perpetration - Borualogo, Ihsana Sabriani; Mubarak, Ali; Dwarawati, Dinda (Jurnal Psikologi, 2025)
Cyberspace has become essential, offering both benefits and challenges, notably the emergence of cyberbullying. This study aimed to assess the prevalence of cyberbullying perpetration and understand how factors like Problematic Internet Use (PIU), stress, loneliness, social media duration, and frequency of fighting contribute among middle school students. It also examined subjective well-being (SWB). Selected through cluster random sampling, the study involved 768 students (50.5% girls, 49.5% boys) aged 12-16 from 16 middle schools in Bandung City (M age = 14.02). Data collection utilized the General Problematic Internet Use Scale 2 (GPIUS2), stress and loneliness scales, a questionnaire on social media use duration and school fights frequency, Children’s World Subjective Well-Being Scale 5 items (CW-SWBS5), and the Cyberbullying Offending Scale. Data were analyzed using descriptive methods and linear regression. Findings highlighted that mood regulation (p = .028), negative PIU outcomes (p = .003), stress (p = .004), loneliness (p = .003), social media duration (p = .036), and school fights frequency (p = .000) predict cyberbullying. More boys (24.1%) engage in cyberbullying than girls (16.5%). Generally, girls reported lower SWB scores (M = 67.17) than boys (M = 74.59). Parents and teachers should make efforts to prevent both girls and boys from engaging in cyberbullying, in order to help them maintain their SWB at an above-average level.